Organohalogenated contaminants in nestlings of white-tailed eagles (Haliaeetus albicilla): Plasma concentrations and possible influences on biomarkers of health - Sletten, Silja (UiT Norges arktiske universitet, 2014)
Biomagnifying organohalogenated contaminants (OCHs) may have adverse effects on the health of birds, especially in marine avian top predators that accumulates high loads of such contaminants. Contaminants may impact the immune system by impairment of the humoral immunity and also influence the antioxidant enzyme activity. Moreover, developmental conditions may affect the shortening of telomeres, one of the main mechanism explaining cell senescence, and it is proven that birds in growth have their telomeres influenced by among other the amount of oxidative stress during their development. To examine the potential effects of organohalogenated contaminants (OCHs) on physiological biomarkers of health, OCHs with different physiochemical properties were related to individual variations in humoral immunity (immunoglobulin Y levels), superoxide dismutase enzyme (SOD) activity, and telomere length in nestlings (n = 35) of white-tailed eagles (Haliaeetus albicilla) in northern Norway. Different organochlorines (OCs) and perfluoroalkylated substances (PFASs) were measured in blood plasma of 7-8 weeks old nestlings, demonstrating higher concentrations of the emerging contaminants (PFASs), notably PFOSli (mean = 40.91 ng/g ww), compared to legacy contaminants (OCs). There were no relationships between the contaminant loadings and plasma immunoglobulin Y (IgY) levels. Moreover, differences between years were found for the telomere length, which was not due to contaminant loadings, but more likely a result of the developmental conditions between the two years sampling took place. However, there were significant and negative relationships between the OC loadings and the super oxidative enzyme (SOD) activity (p<0.01). This suggest that legacy OCs are challenging the antioxidant capacity in nestlings of white-tailed eagles.